Pyoderma gangrenosum in children. - Habibi, Y.; El Fatoiki, F.Z.; Hali, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2024)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis that manifests as painful inflammatory skin ulcerations. It can be isolated or associated with other inflammatory diseases, especially intestinal or joint diseases. An isolated case is presented in a 12-year-old girl, who presented initial diagnostic difficulties, but responded well to systemic corticosteroid therapy.